Quality of life of family caregivers of cancer patients in Singapore and globally - Lim, Haikel A (Singapore Med J, 2017)
INTRODUCTION: Family caregivers of cancer patients often suffer from impaired quality of life (QOL) due to stress arising from the responsibility of caregiving. Most research on such QOL impairments was conducted in Western populations. Thus, this exploratory study sought to (a) examine the QOL levels of family caregivers of cancer patients in an Asian population in Singapore, in relation to caregivers from other countries within and outside of Asia; and (b) investigate the association between sociodemographic factors and QOL impairments in family caregivers in Singapore. METHODS: A total of 258 family caregivers of cancer patients who were receiving outpatient treatment completed the Caregiver Quality of Life Index-Cancer (CQOLC) and a sociodemographic survey. We compared the published CQOLC total scores from Turkey, Iran, Taiwan, South Korea, the United Kingdom, the United States and Canada with the Singapore dataset and examined the demographic relationships. RESULTS: Caregivers in Singapore and Asia had lower CQOLC total scores than their Western counterparts. Caregivers who were male, of Chinese ethnicity, had parental relationships with their care recipient, or cared for advanced-stage cancer patients were found to have impaired QOL. CONCLUSION: The findings of this study highlight possible areas in which support can be provided for family caregivers of cancer patients, and underscore the need to reconcile cultural diversity, values, societal expectations and demographic characteristics in Singapore.